1982
DOI: 10.1007/bf00253742
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and insulin changes following a renoportal shunt in streptozotocin diabetic rats with pancreatic islet isografts under the kidney capsule

Abstract: Summary. The effect on glucose metabolism of altering the site of the venous drainage of an isograft of isolated adult islets implanted beneath the renal capsule, from the systemic circulation to the portal circulation was determined in streptozotocininduced diabetic rats. Reversal of diabetes was accomplished by the transplantation of 1000-1200 isolated islets beneath the left kidney capsule. The rate of fall of the glucose concentration (as expressed by the K value) was found to be significantly decreased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…However, this does not apply to other rat strains (21) or other species (22). Metabolic advantages have been claimed for grafts with portal venous compared with systemic venous drainage (23,24). However, in a study comparing the efficacy of kidney subcapsular and intraportal islets in normalizing the glucose metabolism, there was no superiority for either site, which is in agreement with our results (25).…”
Section: Discussionsupporting
confidence: 91%
“…However, this does not apply to other rat strains (21) or other species (22). Metabolic advantages have been claimed for grafts with portal venous compared with systemic venous drainage (23,24). However, in a study comparing the efficacy of kidney subcapsular and intraportal islets in normalizing the glucose metabolism, there was no superiority for either site, which is in agreement with our results (25).…”
Section: Discussionsupporting
confidence: 91%
“…Critical data in this study are the insulin extractions from the pancreases of all the animals and from the grafts. Previous studies addressing the question of portal insulin drainage (Kemp et al, 1973;Feldman et al, 1977;Brown et al, 1979;Reece-Smith et al, 1982) did not determine the final total insulin content in the animal. Without knowing how much islet tissue remains, it is impossible to assess accurately the efficacy of the graft in handling a metabolic challenge.…”
Section: Discussionmentioning
confidence: 98%
“…However, these grafts drained insulin into the systemic venous circulation and therefore the physiological first-pass of the hormone through the liver was absent (Madison et al, 1958;Blackard and Nelson, 1971;Felig, 1975). Some studies from other laboratories have suggested that portal venous drainage is more effective in controlling diabetes than insulin secreted into the systemic circulation (Kemp et al, 1973;Brown et aL, 1979;Reece-Smith, McShane and Morris, 1982). However, recently Kruszynska, Home and Alberti (1985a,b) reported the ability to achieve consistent euglycaemia with systemically draining Abbreviations used in this paper: GHb, glycosylated haemoglobin; IP, intraperitoneal; RBG, random blood glucose; and STZ, streptozotocin.…”
Section: Introductionmentioning
confidence: 99%
“…Basal glucose and insulin levels in animals with grafts to the spleen were similar to those in controls, but they were significantly higher in animals with grafts to the liver and to the kidney. The increased basal insulin levels seen after transplantation to the kidney can be attributed to the absence of the first-pass insulin extraction by the liver as a consequence of systemic instead of portal venous drainage [6,[19][20][21]. Hyperinsulinaemia, after transplantation to the liver, cannot be attributed to an absent first-pass extraction of insulin, but there is substantial evidence to suggest that this extraction is quantitatively reduced.…”
Section: Discussionmentioning
confidence: 99%
“…As islets differ considerably in size [3,4], seemingly similar graft sizes, when defined by the nmnber of transplanted islets, may well represent a considerable difference in the actual number of Beta cells of the islet grafts. In addition, the differing results between the transplant sites have been attributed to efficacy of engraftment after islet transplantation [5] and to the route of venous drainage of insulin by the endocrine graft, i. e. to the portal or to the systemic circulation [6][7][8]. However, the individual influence either of graft size or of properties related to the graft site on the reported graft function cannot easily be distinguished.…”
mentioning
confidence: 99%